In vitro apatite mineralization and heat generation of magnetite-reduced graphene oxide nanocomposites for hyperthermia treatment - Miyazaki, Toshiki; Akaike, Jun; Kawashita, Masakazu; Lim, Hong Ngee (Elsevier BV, 2019)
Nanocomposites of magnetite (Fe3O4) and reduced graphene oxide (rGO) generate heat under an alternating magnetic field and therefore have potential applications as thermoseeds for cancer hyperthermia treatment. However, the properties of such nanocomposites as biomaterials have not been sufficiently well characterized. In this study, the osteoconductivity of Fe3O4-rGO nanocomposites of various compositions was evaluated in vitro in terms of their apatite-forming ability in simulated body fluid (SBF). Furthermore, the heat generation of the nanocomposites was measured under an alternating magnetic field. The apatite-forming ability in SBF improved as the Fe3O4 content in the nanocomposite was increased. As the Fe3O4 content was increased, the nanocomposite not only rapidly raised the surrounding temperature to approximately 100 °C, but the specific absorption rate also increased. We assumed that the ionic interaction between the Fe3O4 and rGO was enhanced and that Brown relaxation was suppressed as the proportion of rGO in the nanocomposite was increased. Consequently, a high content of Fe3O4 in the nanocomposite was effective for improving both the osteoconductivity and heat generation characteristics for hyperthermia applications.